2019
DOI: 10.1017/s1368980018004032
|View full text |Cite
|
Sign up to set email alerts
|

A practical solution to improve the nutritional balance of Korean dine-out menus using linear programming

Abstract: ObjectiveWe analysed optimal nutrient levels using linear programming (LP) to reveal nutritional shortcomings of Korean dine-out meals and to stress the importance of fruits and dairy products for maintaining a healthy diet.DesignLP models that minimize deviation from recommended nutrient values were formulated to analyse deficiency or excess of nutrients under the best situation.SettingKorean dine-out menus and nutritional information were taken from the nutrient composition tables for dine-out menus develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…However, in the 2016-2018 dataset, Western dietary patterns based on meat and alcohol (Topic 1), or consisting of fried, processed foods and sugar-sweetened beverages (Topic 3), and a traditional dietary pattern (Topic 2) were observed. Dietary patterns and changes in food intake among Korean adults were similar to those from previous studies (4,11,12,17). Studies using the KNHANES dataset examined during the same period demonstrated that the major dietary patterns composed of white rice and Kimchi, or grains, vegetables, and fish were extracted using factor analysis (11,17).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, in the 2016-2018 dataset, Western dietary patterns based on meat and alcohol (Topic 1), or consisting of fried, processed foods and sugar-sweetened beverages (Topic 3), and a traditional dietary pattern (Topic 2) were observed. Dietary patterns and changes in food intake among Korean adults were similar to those from previous studies (4,11,12,17). Studies using the KNHANES dataset examined during the same period demonstrated that the major dietary patterns composed of white rice and Kimchi, or grains, vegetables, and fish were extracted using factor analysis (11,17).…”
Section: Discussionsupporting
confidence: 74%
“…Western dietary patterns are characterized by high intakes of meat, fried foods, refined grains, and added sugars, which may produce unfavorable health outcomes (19)(20)(21)(22). Frequent eating out is associated with a higher intake of total energy, fat, saturated fat, cholesterol, and sodium, and a lower intake of dietary fiber (4,23). Therefore, the shift in dietary patterns should be continuously monitored, and whether the associated changes produce healthy outcomes among Koreans should be checked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The author, therefore, deemed these slight deviations from a single RDA to be acceptable. Scenario 2Bd (Panel D) is a very palatable breakfast menu, as determined by the meal being available in nearly every American breakfast restaurant [34]. All Scenario 2 lunch menus (Scenarios 2La through 2Ld) are shown in Table 8.…”
Section: Scenario 2 Breakfastmentioning
confidence: 99%